1996
DOI: 10.1093/oxfordjournals.aje.a008653
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Origin and Neural Tube Defects in Houston/Harris County, Texas: II. Risk Factors

Abstract: Several investigators have reported Hispanics to be at elevated risk for neural tube defects (anencephaly and spina bifida). Factors contributing to this risk have not been established. The authors conducted a case-control study of neural tube defects (NTDs) among births occurring in Harris County, Texas, from April 1, 1989, through December 31, 1991. Through the use of multiple ascertainment methods, 59 cases of anencephaly and 32 cases of spina bifida were detected. Controls (n = 451) were sampled for the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1
4

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 21 publications
1
38
1
4
Order By: Relevance
“…Since folate deficiency during the first trimester of pregnancy is associated with an increased risk of neural tube defects in the developing fetus (43)(44)(45), it is possible that some instances of high rates of occurrence of these birth defects unexplained by known causes might be linked to dietary exposure to fumonisin B 1 . For instance, high rates of neural tube defects have been observed in Cameron County, TX from 1990 to 1991 (46,47) and in Harris County, TX from 1989 to 1991 (48,49). The prevalence of these birth defects was high among Hispanics (48), for whom corn and corn products are expected to represent a sizable portion of their diet.…”
Section: Discussionmentioning
confidence: 99%
“…Since folate deficiency during the first trimester of pregnancy is associated with an increased risk of neural tube defects in the developing fetus (43)(44)(45), it is possible that some instances of high rates of occurrence of these birth defects unexplained by known causes might be linked to dietary exposure to fumonisin B 1 . For instance, high rates of neural tube defects have been observed in Cameron County, TX from 1990 to 1991 (46,47) and in Harris County, TX from 1989 to 1991 (48,49). The prevalence of these birth defects was high among Hispanics (48), for whom corn and corn products are expected to represent a sizable portion of their diet.…”
Section: Discussionmentioning
confidence: 99%
“…Our interest in the population in Texas stems from reports of increased risk of NTD, especially among Hispanics [Can®eld et al, 1996a[Can®eld et al, , 1996b. Some studies reported low folate intake among Hispanics and African-Americans [Wright et al, 1998;Ford and Ballew, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…[71617] Neural tube defects are etiologically heterogeneous[21819] and the epidemiology of neural tube defects is complex. [13] Many risk factors associated with increased risk for neural tube defects have been identified, including folic acid deficiency,[13] older or very young mothers,[13] modestly increased risk in primiparous,[11] previous spontaneous abortions,[20] short intervals between pregnancies,[21] multiple gestations,[22232425] maternal obesity and elevated body mass index,[262728] maternal diabetes,[20] lower socioeconomic status,[13] tea use in the period before and during the first trimester,[29] zinc deficiency, lead, and high levels of organic matter[30313233] and drugs (including anti-epileptic medications). [13]…”
Section: Discussionmentioning
confidence: 99%